Commercialisation of Intellectual Property: A Comparative Analysis of Georgia and Estonia - Tkeshelashvili Ketevan; Dutt Pawan Kumar; Gurgenidze Miranda (TalTech Journal of European Studies)
Commercialisation of intellectual property (IP) constitutes a vital part of a state’s economy and signifi cantly contributes to the development and success of any innovative project. At the same time, commercialisation of IP is directly linked to the adopted legislation on patent rights as it regulates the protection and exploitation of IP. This article seeks to compare the IP commercialisation frameworks in Georgia and Estonia and identify the challenges encountered in patent protection mechanisms in Georgia. Estonia and Georgia are both located in the Eastern European region and share similar legal systems and constitutions. By aligning its legislative framework with European Union standards and supporting universities and fostering a culture of innovation, Estonia sets a notable example in IP commercialisation. However, Georgia’s legislative framework still lacks certain elements that are crucial for developing IP commercialisation. The low number of registered patent applications in Georgia indicates the challenges and obstacles in this fi eld. The comparison of legal frameworks and practices in these countries can provide important insights into the challenges and solutions in IP commercialisation. The article examines how inefficient legislative framework leads to inconsistent patent protection mechanisms in Georgia, creating barriers in IP commercialisation, while underlining Estonia’s success in innovation and the establishment of a progressive IP commercialisation landscape.